NASA Online TV coverage of the 2017 presidential election in Kenya: a public sphere analysis - Langat, Patrick (My University, 2021)
This study focuses on the 2017 elections in Kenya, an election that was from very early in the presidential race referred to as the social media election (Nyabola, 2018). This was not just because of the way the candidates had used the platform, but also the way voters were sufficiently engaged on various platforms, and about various issues (2018: 190). This study examined how the National Super Alliance (NASA), led by one of the presidential candidates, former Kenyan prime minister, Raila Odinga, used social media in the 2017 presidential elections in Kenya. Specifically, the study examined the content and themes carried by the NASA Online TV, a platform used by the NASA Coalition to broadcast its rallies and host panel discussions on a wide variety of issues. The NASA Online TV packaged itself as “a people-driven channel whose content direction and style comes directly from the people.” While the study gives an outline of the live rallies streamed, its main focus is the opinion panels where the issues being addressed in the study of content, themes, and style and format will come out more vividly, and in a way that can be studied. The study sampled the content produced by NASA online TV using a sequential sampling of every 10th panel discussion video uploaded, with the aim of studying the kind of publics the online TV created, the content and themes it favoured, as well as examine ways in which the NASA Online TV used this platform to steer the debate, and how this engagement played out. The study found that the channel created a situation where discussions by its viewers was not geared towards a rational critical debate, but one that had name calling and passions with no attempt to substantiate arguments with facts. The study also showed a great deal of protectionism where while the formation of NASA Online TV itself was a result of being ‘othered’ by the mainstream media, it led to a situation where any divergent opinion was locked out. This led to a situation that scholars have called echo-chambers where the discussions and the usage itself makes it incredibly difficult, if not impossible, for any dissenting views to be discussed in such spaces (Pariser, 2011)
A thesis submitted in partial fulfilment of the requirements for the award of a degree in Master of Arts in Journalism and Media Studies, at the Faculty of Humanities, University of the Witwatersrand, 2021